Technology money supply and economic growth simultaneously in islamic banks in Indonesia - Mila Naeruz (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The expansion of digital financial technologies has fundamentally reshaped monetary systems in emerging economies, yet the structural interaction between e-money, money supply, Islamic banking, and economic growth remains theoretically fragmented. Existing studies predominantly adopt partial or linear approaches, overlooking the endogenous and simultaneous nature of these relationships. Aims: This study aims to develop a structural simultaneous equation model to capture the dynamic and reciprocal interactions among digital financial adoption, monetary expansion, Islamic banking performance, and economic growth. It contributes to mathematical and quantitative economic modeling by addressing endogeneity within a multi-equation financial system. Methods: Using quarterly time-series data from 2004 to 2024, this study employs a Two-Stage Least Squares (2SLS) estimation framework to identify causal relationships within an endogenous system. The model explicitly accounts for structural interdependence among variables, ensuring consistent parameter estimation under simultaneity conditions. Results: The results reveal that technological adoption and labor productivity significantly strengthen Islamic banking performance, while e-money exerts a dual structural effect by expanding money supply but weakening direct banking productivity. Furthermore, money supply and digital financial expansion positively influence economic growth, whereas Islamic banking shows a non-significant or negative direct effect, indicating a structural inefficiency in financial intermediation. Conclusion: This study uncovers a critical structural paradox in which the expansion of Islamic banking does not proportionally translate into economic growth, despite increased digital financial activity. The findings suggest that digital finance operates primarily through indirect monetary transmission channels rather than direct institutional performance. By modeling the financial system as an endogenous and simultaneous structure, this research advances the theoretical understanding of financial intermediation inefficiencies and provides a more rigorous quantitative framework for analyzing the complex interplay between digital finance and macroeconomic outcomes.